2009
DOI: 10.1038/cdd.2009.154
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-dependent generation of reactive oxygen species in human astrocytoma cells contributes to resistance to TRAIL-mediated apoptosis

Abstract: Tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL), a member of the TNF family of cytokines, causes apoptosis by caspase activation in various cell types, particularly in transformed cells. Numerous types of tumors are relatively resistant to TRAIL-induced cytotoxicity; however, the reasons for this are not yet fully understood. We report here a new signal transduction pathway involving protein kinase Cd (PKCd), NADPH oxidase 4 (NOX4) and reactive oxygen species (ROS), that inhibits caspase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
4
26
0
2
Order By: Relevance
“…Previous studies demonstrated that TRAIL treatment triggers the production of reactive oxygen species (ROS), resulting in intracellular oxidizing conditions. 31 Interestingly, we observed that in vitro binding of Prx6 to caspase-10 was decreased by increased ROS level with the treatment of hydrogen peroxide, but was increased by decreased ROS level with the treatment of ROS scavenger, dithiothreiton (DTT) (Supplementary Figure 3). Thus, we propose a hypothesis that cytosolic accumulation of ROS also may reduce the binding affinity of Prx6 to DED caspase and enhance the chances of FADD to interact with DED caspases to form DISC.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies demonstrated that TRAIL treatment triggers the production of reactive oxygen species (ROS), resulting in intracellular oxidizing conditions. 31 Interestingly, we observed that in vitro binding of Prx6 to caspase-10 was decreased by increased ROS level with the treatment of hydrogen peroxide, but was increased by decreased ROS level with the treatment of ROS scavenger, dithiothreiton (DTT) (Supplementary Figure 3). Thus, we propose a hypothesis that cytosolic accumulation of ROS also may reduce the binding affinity of Prx6 to DED caspase and enhance the chances of FADD to interact with DED caspases to form DISC.…”
Section: Discussionmentioning
confidence: 94%
“…The ROS generation likely played a critical role in the induction of apoptosis of NPC cells because NAC, a ROS scavenger, could markedly reduce the sub-G 1 cell populations, in line with previously reported function of ROS generation in various cancer cell types upon treatment with bortezomib/SAHA (13)(14)(15)(16)19). We sought to clarify the relationship between ROS generation and caspase-dependent apoptosis in the NPC cells as conflicting data on the link between ROS generation and caspase activation have been reported in the literature (33,34). Our data showed that ROS generation resulted in caspase activation and subsequent apoptosis of NPC cells because NAC effectively reduced caspase activation, whereas Z-VAD-FMK failed to reduce ROS production.…”
Section: Discussionmentioning
confidence: 97%
“…We demonstrated that treatment of OSCC cells with a proteasome inhibitor significantly enhanced TRAIL-mediated apoptosis. Molecules involved in TRAIL-mediated apoptosis that are regulated by the ubiquitin-proteasome pathway include members of the death receptor, Bcl-2 (28,29), and IAP families (30,31), and inhibitors of κB (IκB) (23,32). Furthermore, proteasome inhibitors can also decrease c-FLIP protein levels in cells, resulting in induced apoptosis signaling caused by increased caspase-8 activation (33)(34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%